El Comercio Justo: Factor Clave De Disminución De La Pobreza En La Provincia Los Ríos, Ecuador - Borja, René Mesías Villacrés; Manobanda, Mónica Elizabeth Bonilla; Barragán, Sergio Enrique Fierro; Gortaire, Mario Enrique Escobar (European Scientific Journal, ESJ, 2018)
This paper focuses on the results of the research carried out to determine the incidence of Fair Trade as a factor in reducing the poverty of small cocoa producers in the province of Los Rios, Ecuador. It also aimed to ascertain if there are guaranteed aid that will grant them a more direct access to the market for their products, under fairer and more equitable conditions. A mixed research design was used in the study. The qualitative activity was focused on observation, interviews, compilation of documents, registers, materials, and exchanges developed with cocoa producers to collect the information and know their criteria and opinions on the conditions and standard of living. This, however, was carried out from a quantitative point of view. The greatest amount of information was achieved through a structured survey with the application of a multivariate option questionnaire applied to a sample of 177 farmers. The main results obtained revealed that Fair Trade is a key element in reducing poverty levels as long as it is a fundamental part of the territorial development plans of Decentralized Autonomous Governments at all levels. Also, trade unions provide real support to farmers and they also assert their claims using a more continuous use of development premiums, adjustment of minimum guaranteed prices, and pre-financing.